Two new 2-phenylethylchromones from artificial agarwood by holing method. Issue 12 (2nd December 2021) - Xiang, Pan; Zeng, Yan-Bo; Wang, Hao; Kong, Fan-Dong; Chen, Hui-Qin; Mei, Wen-Li; Dai, Hao-Fu
Abstract: Two new 2-(2-phenylethyl)chromone derivatives (1 –2 ) were isolated from the ethyl acetate extract of artificial agarwood induced by holing method originating from Aquilaria sinensis (Lour.) Gilg, and they were isolated from this genus for the first time. The structures of these two new compounds were elucidated by extensive spectroscopic analyses, including UV, IR, one- and two-dimensional NMR and HRESIMS measurements. Bioassay tests of these two new compounds showed compounds 1 and 2 had weak inhibitory activity against acetylcholinesterase at a concentration of 50.0 μg/ml. Graphical abstract: UF0001